Translating Lexical Collocations in Elemental Movie Subtitles - Anshori, Sakut; Arbain, Arbain; Kendenan, Esriaty Sega; Zain, Abd. Rahman; Khoshimov, Mukhriddin (Langkawi: Journal of The Association for Arabic and English, 2024)
Despite the extensive research on collocation translation, studies examining the influence of translation techniques on translation quality—specifically accuracy, acceptability, and readability—are scarce. This study provides an in-depth analysis of the impact of translation techniques on three aspects of lexical collocation translation quality and offers pertinent insights into evaluating translator competence. Employing a qualitative approach, this research identifies translation patterns within a broader context. Content analysis and Focus Group Discussions (FGD) are utilized to gather and validate two primary types of data: linguistic data in the form of lexical collocations from the subtitles of the film Elemental: Forces of Nature, and translation data including translation techniques and their quality. The collected data is analyzed using Spradley's (1980) analytical model as adapted by Santosa (2017), which encompasses domain, taxonomic, componential, and cultural theme analysis. Findings indicate that the dominance of techniques such as established equivalence, transposition, and modulation significantly contributes to high translation quality, assessed in terms of accuracy (2.8), acceptability (2.89), and readability (2.89). These findings highlight the significance of translator proficiency in managing lexical collocations and present substantial implications for EFL instruction in tackling the difficulties of collocation translation. The TQA instrument in this study assists educators in recognizing and correcting prevalent errors in collocation translation, thereby enhancing students' proficiency in translating intricate texts and fostering critical thinking skills related to source texts and their translations.